The reinvention of beach volleyball - prevalence and effectivity of the swedish jumpset - Link, D. (13. DVS-Sportspiel-Symposium - "Ludo, ergo sum - Vom Kinderspiel bis zum Leistungssport", 2024)
Introduction In the last years, the Swedish world class Team Ahmann / Hellvig (AH) reinvented beach volleyball by introducing the "Swedish Jumpset". They create two options on the second ball contact (Second Ball Option (SBO)) by attacking the second ball or fake attack and fast jumpset. This causes temporal pressure on the opponent block player since attacking position stays unclear quite long. This study focusses on seven research questions including i) how often and in which situations do AH create SBO, ii) which factors influence the decision second ball attack vs. jumpset, iii) is setting quality reduced in SBO?, iv) is block quality reduced in SBO, v) how do AH attack in SBO, vi) how effective is attack in SBO, vii) do opponents adapt to this playing style?